Development of SAVI-Based LKPD to Improve Critical Thinking of V Grade Students of SDIT Wahdatul Ummah - Reni Febriyanti; Alben Ambarita; Rochmiyati Rochmiyati (research, training and philanthropy institution Natural Aceh, 2021)
Purpose of this research and development is to describe the validity and effectiveness of developing student worksheets based on the SAVI learning model in improving students' critical thinking skills. This type of research is research and development that refers to the theory of Borg and Gall. The population of this study was the fifth grade elementary school students in East Metro District and the sample was determined by purposive sampling as many as 40 students divided into experimental and control classes. Data was collected through observation sheets, questionnaires, and test questions. The data analysis technique used is the n-Gain test to determine its effectiveness. The results of the validation of the SAVI-based student worksheets were carried out by material, media and language experts. The results showed that the SAVI-based student worksheet development product was valid and effective for use in the fifth grade student learning process. This was evidenced by the improvement in students' critical thinking after using the SAVI-based student worksheet.